The effect of internal marketing practices in enhancing customer loyalty - an applied study in a sample of private banks in Baghdad Governorate - فائق جواد الإبراهيمي, (Iraqi Journal for Administrative Sciences, 2025)
-Purpose :To determine the effect of internal marketing practice son customer loyalty. - Input /methodology: It was selection of a double sample of directors of banks and their customers, and using a question Nair designed in the light of previous studies, the formulation of scale and tested in the light of a set of statistical methods. - Results: The presence of a significant effect of internal marketing and customer loyalty. - Originality /value: The value of current research in theoretical frameworks of the concept of internal marketing, and then clarify the cognitive foundations of customer loyalty - Keyword: internal marketing practices, and customer loyalty